Patterns in periphyton biomass and community structure in foothill rivers: A comparison between winter and summer rainfall regions - Grainger, Cole Vincent (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2019.